Representation of Lithuanian Citizens in the European Parliament: Between European and National Interests - Rakutienė, Sima; Unikaitė-Jakuntavičienė, Ingrida (Politologija, 2020)
The article analyzes the problem of conflict of European and national interests in the activities of a Member of the European Parliament (MEP). The study seeks answers to the following questions: what factors impact the decision and voting of EP members, elected in Lithuania, in the plenary sessions in the cases of collision of interests, and to what extent the interests of the electorate, national parties, or European political groups are important to MEPs elected in Lithuania. To achieve the goal, first, a review of the scientific literature on the representation of interests in the European Parliament, the issues of conflict of interests is carried out. Next, the theoretical model of the “two-level game,” which is applied in the analysis of an MEP’s activities, is discussed. In the second part of the article, a Lithuanian case study is carried out, analyzing the data of semistructured interviews with MEPs, results of public opinion poll of the Lithuanian population, and other quantitative data. The results show that MEPs elected in Lithuania, like the MEPs elected in other countries, face the problem of a conflict of interests. The inquiry also revealed that an MEP’s decision on how to vote in an EP plenary session depends not only on whether they are a member of the opposition or the ruling party, but also on their personal preferences.
Keywords: European Parliament; ideological, national, European interests; citizens representation; EU political system